Using Ice Cores to Evaluate CMIP6 Aerosol Concentrations Over the Historical Era. Issue 18 (17th September 2022) - Moseid, Kine Onsum; Schulz, Michael; Eichler, Anja; Schwikowski, Margit; McConnell, Joseph R.; Olivié, Dirk; Criscitiello, Alison S.; Kreutz, Karl J.; Legrand, Michel
Abstract: The radiative effect of anthropogenic aerosols is one of the largest uncertainties in Earth's energy budget over the industrial period. This uncertainty is in part due to sparse observations of aerosol concentrations in the pre‐satellite era. To address this lack of measurements, ice cores can be used, which contain the aerosol concentration record. To date, these observations have been under‐utilized for comparison to aerosol concentrations found in state‐of‐the‐art Earth system models (ESMs). Here we compare long term trends in concentrations of sulfate and black carbon (BC) between 15 ice cores and 11 ESMs over nine regions around the world during the period 1850–2000. We find that for sulfate concentration trends model results generally agree with ice core records, whereas for BC concentration the model trends differ from the records. Absolute concentrations of both investigated species are overestimated by the models, probably in part due to representation errors. However, we assume that biases in relative trends are not altered by these errors. Ice cores in the European Alps and Greenland record a maximum BC concentration before 1950, while most ESMs used in this study agree on a post‐1950 maximum. We source this bias to an error in BC emission inventories in Europe. Emission perturbation experiments using NorESM2‐LM support the observed finding that BC concentrations in Northern Greenland ice cores are recording European emissions. Errors in BC emission inventories have implications for all future and past studies where Coupled Model Intercomparison Project Phase 6 historical simulations are compared to observations relevant to aerosol forcing. Key Points: The sulfate ice‐core increase until 1970 and its subsequent decrease is well depicted by models The post‐1950 increase of black carbon (BC) predicted by models is not confirmed by ice‐core trends showing instead an early 20th century maximum Ice cores reveal possible errors in Coupled Model Intercomparison Project Phase 6 emission inventories of BC in Europe